CD8+ T cells produce a dialyzable antigen‐specific activator of dendritic cells. Issue 1 (11th August 2016) - Myles, Ian A.; Zhao, Ming; Nardone, Glenn; Olano, Lisa R.; Reckhow, Jensen D.; Saleem, Danial; Break, Timothy J.; Lionakis, Michail S.; Myers, Timothy G.; Gardina, Paul J.; Kirkpatrick, Charles H.; Holland, Steven M.; et al.
Abstract : Cellular lysates from PPD + donors have been reported to transfer tuberculin reactivity to naïve recipients, but not diphtheria reactivity, and vice versa. A historically controversial topic, the terms "transfer factor" and "DLE" were used to characterize the reactivity‐transferring properties of lysates. Intrigued by these reported phenomena, we found that the cellular extract derived from antigen‐specific memory CD8 + T cells induces IL‐6 from antigen‐matched APCs. This ultimately elicits IL‐17 from bystander memory CD8 + T cells. We have identified that dialyzable peptide sequences, S100a9, and the TCR β chain from CD8 + T cells contribute to the molecular nature of this activity. We further show that extracts from antigen‐targeted T cells enhance immunity to Staphylococcus aureus and Candida albicans . These effects are sensitive to immunization protocols and extraction methodology in ways that may explain past discrepancies in the reproducibility of passive cellular immunity. Abstract : Lysates from CD8 + T cells transfer passive IL‐17‐mediated cellular immunity through elements of the TCR and S100; an opportunity to elucidate the structure, role, and therapeutic potential.